2014
DOI: 10.1186/1746-6148-10-115
|View full text |Cite
|
Sign up to set email alerts
|

High yield production of pigeon circovirus capsid protein in the E. coliby evaluating the key parameters needed for protein expression

Abstract: BackgroundPigeon circovirus (PiCV) is considered to be a viral agent central to the development of young pigeon disease syndrome (YPDS). The Cap protein, a structural protein encoded by the cap (or C1) gene of PiCV, has been shown to be responsible for not only capsid assembly, but also has been used as antigen for detecting antibody when the host is infected with PiCV. The antigenic characteristics of the Cap protein potentially may allow the development of a detection kit that could be applied to control PiC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Currently, gene-engineered vaccines based on the major immunogens like capsid proteins of viruses are under development in both human and veterinary medicine. In recent years, recombinant capsid proteins of various circoviruses like DuCV, PCV2, PBFDV and PiCV have been produced in bacterial, yeast, and baculovirus systems [ 10 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 39 , 40 , 41 ]. Little is known, however, about the immunogenicity of avian circoviruses’ recombinant capsid proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, gene-engineered vaccines based on the major immunogens like capsid proteins of viruses are under development in both human and veterinary medicine. In recent years, recombinant capsid proteins of various circoviruses like DuCV, PCV2, PBFDV and PiCV have been produced in bacterial, yeast, and baculovirus systems [ 10 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 39 , 40 , 41 ]. Little is known, however, about the immunogenicity of avian circoviruses’ recombinant capsid proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional vaccines are mainly composed of live, attenuated, or inactivated pathogens; however, no laboratory protocol has so far been developed for culturing PiCV, and for this reason, the specific immunoprophylaxis of PiCV infections in pigeons is impossible [ 28 ]. Various methods for antigen production for diagnostic tests—PiCV recombinant capsid protein (rCP)—have been developed in recent years [ 10 , 28 , 29 , 30 ]. PiCV rCP could also be a potential candidate as a vaccine antigen, but its immunogenicity has not been confirmed in scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…A specific protocol for the prevention of PiCV infections in pigeons has not yet been developed due to the absence of vaccines targeting this pathogen. In recent years, attempts have been made to develop a recombinant PiCV capsid protein for diagnostic tests and a subunit vaccine against the PiCV (Daum et al 2009;Lai et al 2014;Stenzel et al 2016). This vaccine could protect pigeons against PiCV infection and, possibly, lower the prevalence of YPDS.…”
Section: Diagnosis Treatment and Preventionmentioning
confidence: 99%
“…The data, presented in Figure 3 B, revealed that lower numbers of targets were obtained from genes synthesized artificially ( p = 0.04). Several studies have demonstrated that codon optimization for heterologous production in E. coli can potentially increase recombinant protein expression, especially in sequences of eukaryotic and archaeal origin [ 23 , 24 , 25 , 26 ]. However, other studies revealed that E. coli codon optimization may lead to overexpression of recombinant proteins, thus resulting in a higher tendency to generate insoluble inclusion bodies [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%